2013
DOI: 10.1002/cctc.201200670
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Imaging of SAPO‐34 Molecular Sieves at the Nanoscale: Influence of Steaming on the Methanol‐to‐Hydrocarbons Reaction

Abstract: The effect of a severe steaming treatment on the physicochemical properties and catalytic performance of H‐SAPO‐34 molecular sieves during the methanol‐to‐hydrocarbons (MTH) reaction has been investigated with a combination of scanning transmission X‐ray microscopy (STXM), catalytic testing, and bulk characterization techniques, including ammonia temperature programmed desorption and 27Al and 29Si magic angle spinning nuclear magnetic resonance. For this purpose, two samples, namely a calcined and a steamed H‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 48 publications
2
36
3
Order By: Relevance
“…This behavior was already reported in the literature for more conventional SAPO-34 samples [22][23][24][25]. Briend et al [22] related the lack of long-term stability to the presence of silicon islands, favored by the use of morpholine as template.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…This behavior was already reported in the literature for more conventional SAPO-34 samples [22][23][24][25]. Briend et al [22] related the lack of long-term stability to the presence of silicon islands, favored by the use of morpholine as template.…”
Section: Introductionsupporting
confidence: 70%
“…Recently, Aramburo et al [25] reported no difference with the purely thermally treated samples [31,34,35], i.e., a reduction in acidity with migration of silicon species to silicon islands. However, in an earlier contribution Park et al [37] showed that SAPO-34 thermally treated at 750ºC loses more crystallinity after reaction Theoretical calculations on the role of steaming on clusters of isomorphous zeolite SSZ-13 and SAPO-34 [38] also to support our hypothesis on the effect of steaming on SAPO-34 stability.…”
Section: The 29mentioning
confidence: 99%
See 1 more Smart Citation
“…The physicochemical properties of the H‐SAPO‐34 catalyst material under study have been reported in the previous work of our group 14. Nitrogen physisorption results indicated that the H‐SAPO‐34 sample is mainly microporous with a BET surface area of 594 m 2 g −1 and a micropore volume of 0.22 cm 3 g −1 .…”
Section: Resultsmentioning
confidence: 59%
“…[31][32][33][34][35][36] This multi-technique approach has also been successfully applied to the study of spatiotemporal heterogeneities in for example, individual fluid catalytic cracking catalyst particles of different age, [37] or catalyst powderb efore/after steaming. [38][39][40] UV/Vis and IR micro-spectroscopies are limited in spatialr esolution, but have proven to be valuablet ools for the chemical identification of hydrocarbon deposits;c onfocal fluorescencem icroscopy on the other hand enables their 3D visualisation with ar esolution down to approximately 500 nm. In addition, measurements based on visible absorption with polarised light, [41] or the study of the polarisation of emitted fluorescent light, [42] can be used to reveal the locationa nd specific orientation in the zeolite framework of the chromophore under investigation, and link their formation and presence to specific channel types.…”
mentioning
confidence: 99%